Jihad Virtual: Social Network Analysis Viralisasi Tagar #Julidfisabilillah pada Media Sosial - Arnus, Sri Hadijah (KOMUNIDA : Media Komunikasi dan Dakwah, 2024)
One manifestation of the reaction of Indonesian netizens in response to the aggression carried out by Israel against Palestine was the JulidFisabilillah movement which viralized the hashtag #JulidFisabilillah on social media X (Twitter), so that it became a trending topic in cyberspace. This research aims to see the form of the JulidFisabilallah netizen movement on social media, the network of actors who played a role in the viralization of #JulidFisabilillah and what narratives went viral. This type of research is descriptive qualitative. The data in this research is in the form of online news about the JulidFisabilillah movement as well as secondary data from Drone Emprit Academic, a website analyzing trends in social media movements using big data assisted by AI technology. Data analysis using Social Network Analysis. The results of the research show that the JulidFisabilillah movement provided mental attacks in the form of narratives on social media against pro-Israel groups, which had quite a significant impact. The network of actors who played a role in this movement were Erlangga Greschinov, and Azzam Izzulhaq who was a top Influencer on the X platform who directed netizen attacks on pro-Israel accounts. Mass movements aimed at protesting policies and changing opinions through digital platforms will be an option in the future, therefore it is necessary to provide adequate digital literacy for netizens, especially in Indonesia.